Preparation method of SiO2@BN core-shell structure modified polyetherimide insulating film
By introducing SiO2@BN core-shell structure filler into the polyetherimide insulating film, a heterostructure is formed and a local electric field is constructed, which solves the problems of high flow mobility and breakdown phenomenon in high electric field conditions, and significantly improves the insulation performance and resistance to electric breakdown.
Patent Information
- Application Number
- CN202411914339.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
AI Technical Summary
Traditional polyetherimide (PEI) insulating films have high flow mobility under high electric field conditions, resulting in abnormal increase in conductivity, increasing conductivity loss, and prone to breakdown, affecting the performance and reliability of OLED devices.
SiO2@BN core-shell structure filler is introduced to form a heterostructure in the polyetherimide matrix, and a local electric field is constructed to inhibit the breakdown path, block the movement and transmission of free electrons, and reduce the current density.
It significantly improves the insulation performance and resistance to electric breakdown of the insulating film, extends the life of OLED devices and improves its stability.
Smart Images

Figure CN119775606A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dielectric insulation, and in particular relates to a method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film. Background Art
[0002] With the rapid development of OLED display technology, polyetherimide (PEI) insulating film plays an important role in the manufacturing process due to its excellent heat resistance, electrical insulation performance and chemical stability. However, as OLED technology continues to pursue higher resolution and more complex display effects, more stringent requirements are placed on the electrical insulation performance of PEI films. Under high voltage conditions, the electrical properties of traditional polyetherimide (PEI) films are prone to attenuation, which seriously affects the performance of OLED devices and poses a severe test to their long-term reliability. This is attributed to the high carrier mobility of traditional PEI films under high electric field conditions, which leads to an abnormal increase in conductivity, thereby increasing conductivity losses and limiting its promotion in high-end application fields. What's worse, under high voltage conditions, PEI films are prone to breakdown, which further reduces the stability and service life of the device. These defects are mainly attributed to the excessive migration of free electrons inside the polymer matrix, which causes the failure of insulation performance. Therefore, the existing PEI films have obvious deficiencies in insulation performance and high voltage resistance, and it is difficult to meet the market's growing demand for high-performance electronic devices. In order to effectively address these challenges, it is urgent to develop new insulating materials to significantly improve the insulation properties and electrical breakdown resistance of the film, thereby enhancing the overall performance and reliability of OLED devices. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film.
[0004] In order to solve the above problems existing in the prior art, the present invention provides a method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film, by introducing SiO2@BN core-shell structure filler, forming a heterostructure in the polyetherimide matrix, and constructing a local electric field to suppress the breakdown path. This structure forms an electric field in the opposite direction of the external electric field at the heterojunction interface due to electron transfer, which can effectively offset the effect of the external electric field, and can effectively inhibit the transport of carriers inside the composite medium, reduce the current density of the film, and finally effectively improve the insulation performance of the film. This modified PEI film has great application potential in the field of OLED, especially in improving the stability of the device and extending the life.
[0005] A method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film is specifically completed by the following steps:
[0006] 1. Dissolve hydroxylated silica in deionized water and stir for a period of time at room temperature to obtain a silica solution;
[0007] 2. Add tert-butyl alcohol, melamine powder and boric acid powder to the silica solution in sequence, then heat and stir, then sonicate, and place at room temperature for a period of time to obtain a white hydrogel; freeze-dry the white hydrogel for a period of time to obtain a SiO2@BN precursor powder;
[0008] 3. Put the SiO2@BN precursor powder in a crucible, put it in a tube furnace, and anneal it for a period of time in an argon atmosphere to obtain a SiO2@BN core-shell structure filler;
[0009] 4. dissolving the diamine monomer in an organic solvent, and performing ultrasonic dispersion to obtain a diamine dispersion; adding the SiO2@BN core-shell structure filler to the diamine dispersion, and stirring evenly to obtain a composite solution;
[0010] 5. under low temperature and stirring conditions, adding the dianhydride monomer to the composite solution in batches to obtain a polyetheramic acid colloid;
[0011] 6. The polyetheramide acid colloid is vacuum-bubbled, and then the polyetheramide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven to remove the solvent in the film for a period of time, and then the temperature is increased by thermal gradient to perform imidization treatment, and naturally cooled to room temperature to obtain a SiO2@BN core-shell structure modified polyetherimide insulating film.
[0012] Compared with the prior art, the beneficial effects of the present invention are:
[0013] 1. The present invention aims to improve the insulation performance of polyetherimide film, and solves the problems of high carrier mobility of the current film under high electric field, resulting in increased conductivity and high conductivity loss. In order to effectively reduce the leakage current density inside the film under high electric field, nano-silicon dioxide particles with a wide band gap are introduced into the matrix. The present invention innovatively uses boron nitride to coat the silicon dioxide, effectively blocking the movement and transfer of free electrons between the matrix-filler-matrix, reducing the current density, and improving the insulation performance of the composite material.
[0014] Second, the present invention applies SiO2@BN core-shell structure filler to polyetherimide to obtain a modified polyetherimide insulating film with excellent insulating properties; in view of the problem of insulation failure caused by excessive free electron migration in the polymer matrix, the polyetherimide insulating film is carefully designed from microscopic to mesoscopic structure, and its breakdown performance is studied; the core of the present invention is to prepare a special core-shell structure filler, that is, boron nitride (BN) is successfully coated on the surface of hydroxyl-modified silica (SiO2) nanoparticles; by introducing SiO2@BN core-shell structure filler, a heterostructure can be formed in the polyetherimide matrix, and a local electric field can be constructed to suppress the breakdown path. This structure always has an electric field in the opposite direction of the external electric field due to electron transfer at the heterojunction interface, which can effectively offset the effect of the external electric field, effectively inhibit the transport of carriers inside the film, reduce the current density of the film, and improve the film's anti-electrical breakdown performance. The results show that in the process of preparing SiO2@BN core-shell structure filler, when the ratio of BN to SiO2 is 1:8, BN cannot be successfully coated on the SiO2 surface, and when the ratio is 1:6, the breakdown field strength of 6-SiO2@BN / PEI insulating film reaches 611kV / mm, which is 21% higher than that of pure PEI. This proves that the insulation properties of polymers can be improved by constructing heterogeneous structure design strategies inside polymers, providing a new reference direction for the research of insulating dielectrics. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The figure is a flow chart for preparing the SiO2@BN core-shell structure filler in the present invention;
[0016] Figure 2 This is a flow chart for preparing SiO2@BN / PEI composite film in the present invention;
[0017] Figure 3 XRD test curves of SiO2@BN fillers prepared in Example 1, Example 2, and Example 3, and Weibull distribution diagram of breakdown field strength of SiO2@BN / PEI insulating films prepared in Example 1, Example 2, Example 3, and Comparative Example 1. DETAILED DESCRIPTION
[0018] Specific implementation method 1: This implementation method is a method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film, which is specifically completed by the following steps:
[0019] 1. dissolving hydroxylated silicon dioxide in deionized water and stirring ultrasonically at room temperature for a period of time to obtain a silicon dioxide solution;
[0020] 2. Add tert-butyl alcohol, melamine powder and boric acid powder to the silica solution in sequence, then heat and stir, then sonicate, and place at room temperature for a period of time to obtain a white hydrogel; freeze-dry the white hydrogel for a period of time to obtain a SiO2@BN precursor powder;
[0021] 3. Put the SiO2@BN precursor powder in a crucible, put it in a tube furnace, and anneal it for a period of time in an argon atmosphere to obtain a SiO2@BN core-shell structure filler;
[0022] 4. dissolving the diamine monomer in an organic solvent, and performing ultrasonic dispersion to obtain a diamine dispersion; adding the SiO2@BN core-shell structure filler to the diamine dispersion, and stirring evenly to obtain a composite solution;
[0023] 5. under low temperature and stirring conditions, adding the dianhydride monomer to the composite solution in batches to obtain a polyetheramic acid colloid;
[0024] 6. The polyetheramide acid colloid is vacuum-bubbled, and then the polyetheramide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven to remove the solvent in the film for a period of time, and then the temperature is increased by thermal gradient to perform imidization treatment, and naturally cooled to room temperature to obtain a SiO2@BN core-shell structure modified polyetherimide insulating film.
[0025] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the mass ratio of the hydroxylated silicon dioxide described in step 1 to the volume ratio of deionized water is (0.095 g to 0.57 g): (21 mL to 63 mL); the hydroxylated silicon dioxide described in step 1 is purchased from Beijing Dekedaojin Technology Co., Ltd., and the particle size is 30 nm; the ultrasonic stirring time described in step 1 is 1 h to 2 h. The other steps are the same as those in specific embodiment 1.
[0026] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the usage ratio of tert-butyl alcohol, melamine powder and boric acid powder in step 2 is (29 mL to 87 mL): (0.061 g to 0.183 g): (0.059 g to 0.177 g); the volume ratio of the mass of hydroxylated silicon dioxide in step 1 to the volume ratio of tert-butyl alcohol in step 2 is (0.095 g to 0.57 g): (29 mL to 87 mL). The other steps are the same as those in specific embodiment 1 or 2.
[0027] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the heating and stirring temperature in step 2 is 80°C, the heating and stirring time is 30 min to 50 min, and the ultrasonic time in step 2 is 30 min to 50 min. The other steps are the same as those in specific embodiments 1 to 3.
[0028] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the time of standing at room temperature in step 2 is 30 min to 50 min; the freeze drying temperature in step 2 is -60°C to -50°C, and the freeze drying time is 24h to 48h; boric acid powder is added in batches in step 2. The other steps are the same as those in specific embodiments 1 to 4.
[0029] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the annealing temperature in step 3 is 1400° C. and the annealing time is 3 hours. The other steps are the same as those in specific implementation examples 1 to 5.
[0030] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the diamine monomer described in step 4 is 4,4'-diaminodiphenyl ether; the organic solvent is N-methyl-2-pyrrolidone; the mass ratio of the diamine monomer described in step 4 to the volume ratio of the organic solvent is (1.5g to 4.5g): (18.3mL to 54.9mL); the ultrasonic dispersion time described in step 4 is 5min to 15min. The other steps are the same as those of specific embodiments 1 to 6.
[0031] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the dianhydride monomer described in step five is bisphenol A type diether dianhydride; the mass ratio of the dianhydride monomer to the diamine monomer described in step five is (4.019g-12.057g):(1.5g-4.5g); the mass of the SiO2@BN core-shell structure filler described in step four is 0.5% of the total mass of the diamine monomer and the dianhydride monomer. The other steps are the same as specific embodiments one to seven.
[0032] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 5, 4.019g to 12.057g of dianhydride monomer is added to the composite solution in 6 times, and the addition amount of the 6 times is 2g to 6g, 1g to 3g, 0.5g to 1.5g, 0.3g to 0.9g, 0.1g to 0.3g, 0.119g to 0.357g, and the stirring time after the 6 additions is 10min to 20min, 10min to 20min, 10min to 20min, 10min to 20min, 20min to 40min, 60min to 120min, the temperature of the low temperature described in step 5 is 0℃ to 10℃, and the stirring condition described in step 5 is 3000r / min. The other steps are the same as those of specific embodiments 1 to 8.
[0033] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in step 6, the polyether amide acid colloid is vacuum-bubbled, and then the polyether amide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven at 80°C to remove the solvent in the film for 12h to 18h; in step 6, the process of thermal gradient heating for imidization treatment is: first, keep warm at 150°C for 1h, then keep warm at 200°C for 1h, then keep warm at 250°C for 1h, and finally keep warm at 300°C for 1h. The other steps are the same as those of specific embodiments 1 to 9.
[0034] The following examples are used to verify the beneficial effects of the present invention:
[0035] Example 1: A method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film is specifically completed by the following steps:
[0036] 1. Dissolve 0.095 g of hydroxylated silica in 21 mL of deionized water and stir ultrasonically at room temperature for 1 h to obtain a silica solution;
[0037] The hydroxylated silica described in step 1 was purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 30 nm;
[0038] 2. Add 29 mL of tert-butanol, 0.061 g of melamine powder and 0.059 g of boric acid powder to the silica solution in sequence, then heat and stir at 80 ° C for 30 min, then ultrasonicate for 30 min, and place at 25 ° C for 30 min to obtain a white hydrogel; freeze-dry the white hydrogel for 24 h at a freeze-drying temperature of -50 ° C to obtain a SiO2@BN precursor powder;
[0039] Add boric acid powder three times in step 2;
[0040] 3. The SiO2@BN precursor powder was placed in a crucible, and then placed in a tube furnace, and annealed for 3 hours in an argon atmosphere at a temperature of 1400°C to obtain a SiO2@BN core-shell structure filler (4-SiO2@BN);
[0041] 4. Dissolve 1.5 g of diamine monomer in 18.3 mL of organic solvent, and perform ultrasonication for 5 min to obtain a diamine dispersion; add SiO2@BN core-shell structure filler to the diamine dispersion, stir evenly, and obtain a composite solution;
[0042] The diamine monomer described in step 4 is 4,4'-diaminodiphenyl ether; the organic solvent is N-methyl-2-pyrrolidone;
[0043] 5. Under the stirring conditions of 10° C. and 3000 r / min, 4.019 g of dianhydride monomer was added to the composite solution in portions to obtain a polyether amide acid colloid;
[0044] The dianhydride monomer described in step 5 is bisphenol A diether dianhydride;
[0045] The mass of the SiO2@BN core-shell structure filler described in step 4 is 0.5% of the total mass of the diamine monomer and the dianhydride monomer;
[0046] In step 5, 4.019 g of dianhydride monomer was added to the composite solution in 6 times, the addition amounts of the 6 times were 2 g, 1 g, 0.5 g, 0.3 g, 0.1 g, and 0.119 g, respectively, and the stirring time after the 6 additions was 10 min, 10 min, 10 min, 10 min, 20 min, and 60 min, respectively;
[0047] Sixth, the polyether amide acid colloid is vacuum-bubbled, and then the polyether amide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven to remove the solvent in the film for a period of time, and then the temperature is increased by thermal gradient to perform imidization treatment, and naturally cooled to room temperature to obtain a SiO2@BN core-shell structure modified polyetherimide insulating film (4-SiO2@BN / PEI);
[0048] In step 6, the polyetheramic acid colloid is vacuum-bubbled, and then the polyetheramic acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven at 80° C. to remove the solvent in the film for 12 hours;
[0049] The process of thermal gradient heating for imidization treatment in step six is: first keep warm at 150°C for 1 hour, then keep warm at 200°C for 1 hour, then keep warm at 250°C for 1 hour, and finally keep warm at 300°C for 1 hour.
[0050] Example 2: A method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film is specifically completed by the following steps:
[0051] 1. Dissolve 0.19 g of hydroxylated silica in 42 mL of deionized water and stir ultrasonically at room temperature for 2 h to obtain a silica solution;
[0052] The hydroxylated silica described in step 1 was purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 30 nm;
[0053] 2. Add 58 mL of tert-butyl alcohol, 0.081 g of melamine powder and 0.079 g of boric acid powder to the silica solution in sequence, then heat and stir at 80 ° C for 40 min, then ultrasonicate for 40 min, and place at 25 ° C for 40 min to obtain a white hydrogel; freeze-dry the white hydrogel for 36 h at a freeze-drying temperature of -55 ° C to obtain a SiO2@BN precursor powder;
[0054] Add boric acid powder three times in step 2;
[0055] 3. The SiO2@BN precursor powder was placed in a crucible, and then placed in a tube furnace, and annealed for 3 hours in an argon atmosphere at a temperature of 1400°C to obtain a SiO2@BN core-shell structure filler (6-SiO2@BN);
[0056] 4. Dissolve 3 g of diamine monomer in 36.6 mL of organic solvent, and perform ultrasonication for 10 min to obtain a diamine dispersion; add SiO2@BN core-shell structure filler to the diamine dispersion, stir evenly, and obtain a composite solution;
[0057] The diamine monomer described in step 4 is 4,4'-diaminodiphenyl ether; the organic solvent is N-methyl-2-pyrrolidone;
[0058] 5. Under stirring conditions of 5° C. and 3000 r / min, 8.038 g of dianhydride monomer was added to the composite solution in portions to obtain a polyether amide acid colloid;
[0059] The dianhydride monomer described in step 5 is bisphenol A diether dianhydride;
[0060] The mass of the SiO2@BN core-shell structure filler described in step 4 is 0.5% of the total mass of the diamine monomer and the dianhydride monomer;
[0061] In step 5, 8.038 g of dianhydride monomer was added to the composite solution in 6 times, the addition amounts of the 6 times were 4 g, 2 g, 1 g, 0.6 g, 0.2 g, and 0.238 g, respectively, and the stirring time after the 6 additions was 15 min, 15 min, 15 min, 15 min, 30 min, and 90 min, respectively;
[0062] Sixth, the polyether amide acid colloid is vacuum-bubbled, and then the polyether amide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven to remove the solvent in the film for a period of time, and then the temperature is increased by thermal gradient to perform imidization treatment, and naturally cooled to room temperature to obtain a SiO2@BN core-shell structure modified polyetherimide insulating film (6-SiO2@BN / PEI);
[0063] In step 6, the polyetheramic acid colloid is vacuum-bubbled, and then the polyetheramic acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven at 80° C. to remove the solvent in the film for 16 hours;
[0064] The process of thermal gradient heating for imidization treatment in step six is: first keep warm at 150°C for 1 hour, then keep warm at 200°C for 1 hour, then keep warm at 250°C for 1 hour, and finally keep warm at 300°C for 1 hour.
[0065] Example 3: A method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film is specifically completed by the following steps:
[0066] 1. Dissolve 0.57 g of hydroxylated silica in 63 mL of deionized water and stir ultrasonically at room temperature for 1 h to obtain a silica solution;
[0067] The hydroxylated silica described in step 1 was purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 30 nm;
[0068] 2. Add 87 mL of tert-butanol, 0.183 g of melamine powder and 0.177 g of boric acid powder to the silica solution in sequence, then heat and stir at 80 ° C for 50 min, then ultrasonicate for 50 min, and place at 25 ° C for 50 min to obtain a white hydrogel; freeze-dry the white hydrogel for 48 h at a freeze-drying temperature of -60 ° C to obtain a SiO2@BN precursor powder;
[0069] Add boric acid powder three times in step 2;
[0070] 3. The SiO2@BN precursor powder was placed in a crucible, and then placed in a tube furnace, and annealed for 3 hours in an argon atmosphere at a temperature of 1400°C to obtain a SiO2@BN core-shell structure filler (8-SiO2@BN);
[0071] 4. Dissolve 4.5 g of diamine monomer in 54.9 mL of organic solvent, and perform ultrasonication for 15 min to obtain a diamine dispersion; add SiO2@BN core-shell structure filler to the diamine dispersion, stir evenly, and obtain a composite solution;
[0072] The diamine monomer described in step 4 is 4,4'-diaminodiphenyl ether; the organic solvent is N-methyl-2-pyrrolidone;
[0073] 5. Under the stirring conditions of 0°C and 3000 r / min, 12.057 g of dianhydride monomer was added to the composite solution in portions to obtain a polyether amide acid colloid;
[0074] The dianhydride monomer described in step 5 is bisphenol A diether dianhydride;
[0075] The mass of the SiO2@BN core-shell structure filler described in step 4 is 0.5% of the total mass of the diamine monomer and the dianhydride monomer;
[0076] In step 5, 12.057 g of dianhydride monomer was added to the composite solution in 6 times, the addition amounts of the 6 times were 6 g, 3 g, 1.5 g, 0.9 g, 0.3 g, and 0.357 g, respectively, and the stirring time after the 6 additions was 20 min, 20 min, 20 min, 20 min, 40 min, and 120 min, respectively;
[0077] Sixth, the polyether amide acid colloid is vacuum-bubbled, and then the polyether amide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven to remove the solvent in the film for a period of time, and then the temperature is increased by thermal gradient to perform imidization treatment, and naturally cooled to room temperature to obtain a SiO2@BN core-shell structure modified polyetherimide insulating film (8-SiO2@BN / PEI);
[0078] In step 6, the polyetheramic acid colloid is vacuum-bubbled, and then the polyetheramic acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven at 80° C. to remove the solvent in the film for 18 hours;
[0079] The process of thermal gradient heating for imidization treatment in step six is: first keep warm at 150°C for 1 hour, then keep warm at 200°C for 1 hour, then keep warm at 250°C for 1 hour, and finally keep warm at 300°C for 1 hour.
[0080] Comparative Example 1:
[0081] During the synthesis of polyetherimide, SiO2@BN core-shell structure filler was not added to prepare a pure polyetherimide comparison sample. The specific steps are as follows:
[0082] Step 1, dissolving 1.5 g of 4,4'-diaminodiphenyl ether in 18.3 mL of N-methyl-2-pyrrolidone solvent and ultrasonicating for 5 min to obtain a diamine dispersion;
[0083] Step 2, weighing 4.019 g of bisphenol A diether dianhydride, adding it to the diamine dispersion in 6 times, and maintaining mechanical stirring at a low temperature of 3000 rpm; the added amounts were 2 g, 1 g, 0.5 g, 0.3 g, 0.1 g, and 0.119 g, respectively, and the stirring time after each addition was 10 min, 10 min, 10 min, 10 min, 20 min, and 60 min, respectively, to obtain a polyamic acid colloid;
[0084] Step 3, vacuum bubble the polyamic acid colloid, then use a scraper to evenly coat the polyamic acid colloid on a glass plate, and then place it in a high-temperature oven at 80°C to remove the solvent in the film for 12 hours, keep it warm at 150°C for 1 hour, keep it warm at 200°C for 1 hour, keep it warm at 250°C for 1 hour, keep it warm at 300°C for 1 hour, and wait for natural cooling to obtain a polyetherimide film (PEI).
[0085] Figure 3 XRD test curves of SiO2@BN fillers prepared in Example 1, Example 2, and Example 3, and Weibull distribution diagrams of breakdown field strength of SiO2@BN / PEI insulating films prepared in Example 1, Example 2, Example 3, and Comparative Example 1;
[0086] Depend on Figure 3 It can be seen that in the process of preparing core-shell structure fillers, when the ratio of BN to SiO2 is 1:8, BN cannot be successfully coated on the SiO2 surface (Example 3). After introducing SiO2@BN core-shell structure fillers into the PEI matrix, the breakdown field strength of the composite film is significantly improved at both room temperature and high temperature compared with the pure PEI film. This is due to the fact that the SiO2 core layer has high insulation properties and a wide band gap, and can also form a heterogeneous structure in the matrix to construct a local electric field to suppress the breakdown path, inhibit the transport of carriers inside the film, reduce the current density of the film, and increase the breakdown field strength of the film. Among them, the breakdown field strength of 6-SiO2@BN / PEI is the highest, at 611kV / mm, which is 21% higher than the 505kV / mm of the pure PEI film at room temperature.
Claims
1. A method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film, characterized in that The preparation method is specifically completed according to the following steps:
1. dissolving hydroxylated silicon dioxide in deionized water and stirring ultrasonically at room temperature for a period of time to obtain a silicon dioxide solution; 2. Add tert-butyl alcohol, melamine powder and boric acid powder to the silica solution in sequence, then heat and stir, then sonicate, and place at room temperature for a period of time to obtain a white hydrogel; freeze-dry the white hydrogel for a period of time to obtain a SiO2@BN precursor powder; 3. Put the SiO2@BN precursor powder in a crucible, put it in a tube furnace, and anneal it for a period of time in an argon atmosphere to obtain a SiO2@BN core-shell structure filler; 4. dissolving the diamine monomer in an organic solvent, and performing ultrasonic dispersion to obtain a diamine dispersion; adding the SiO2@BN core-shell structure filler to the diamine dispersion, and stirring evenly to obtain a composite solution; 5. under low temperature and stirring conditions, adding the dianhydride monomer to the composite solution in batches to obtain a polyetheramic acid colloid; 6. The polyetheramide acid colloid is vacuum-bubbled, and then the polyetheramide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven to remove the solvent in the film for a period of time, and then the temperature is increased by thermal gradient to perform imidization treatment, and naturally cooled to room temperature to obtain a SiO2@BN core-shell structure modified polyetherimide insulating film.
2. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that The mass ratio of the hydroxylated silica described in step one to the volume ratio of deionized water is (0.095g-0.57g):(21mL-63mL); the particle size of the hydroxylated silica described in step one is 30nm; the ultrasonic stirring time described in step one is 1h-2h.
3. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that The dosage ratio of tert-butanol, melamine powder and boric acid powder described in step 2 is (29mL~87mL):(0.061g~0.183g):(0.059g~0.177g); the volume ratio of the mass of hydroxylated silica described in step 1 to the volume ratio of tert-butanol described in step 2 is (0.095g~0.57g):(29mL~87mL).
4. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that The temperature of the heating and stirring in step 2 is 80° C., and the time of the heating and stirring is 30 min to 50 min; the time of the ultrasound in step 2 is 30 min to 50 min.
5. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that The time of standing at room temperature in step 2 is 30 min to 50 min; the freeze-drying temperature in step 2 is -60°C to -50°C, and the freeze-drying time is 24h to 48h; and boric acid powder is added in batches in step 2.
6. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that The annealing temperature in step 3 is 1400° C. and the annealing time is 3 h.
7. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that The diamine monomer described in step 4 is 4,4'-diaminodiphenyl ether; the organic solvent is N-methyl-2-pyrrolidone; the mass ratio of the diamine monomer described in step 4 to the volume ratio of the organic solvent is (1.5g~4.5g):(18.3mL~54.9mL); the ultrasonic dispersion time described in step 4 is 5min~15min.
8. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that The dianhydride monomer described in step five is bisphenol A diether dianhydride; the mass ratio of the dianhydride monomer to the diamine monomer described in step five is (4.019g~12.057g):(1.5g~4.5g); the mass of the SiO2@BN core-shell structure filler described in step four is 0.5% of the total mass of the diamine monomer and the dianhydride monomer.
9. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that In step five, 4.019g to 12.057g of dianhydride monomer is added to the composite solution in 6 times, and the addition amounts of the 6 times are 2g to 6g, 1g to 3g, 0.5g to 1.5g, 0.3g to 0.9g, 0.1g to 0.3g, and 0.119g to 0.357g, respectively. The stirring time after the 6 additions is 10min to 20min, 10min to 20min, 10min to 20min, 10min to 20min, 10min to 20min, 20min to 40min, and 60min to 120min, respectively; the low temperature described in step five is 0°C to 10°C; the stirring condition described in step five is 3000r / min.
10. The method for preparing a SiO2@BN core-shell structure modified polyetherimide insulating film according to claim 1, characterized in that In step six, the polyether amide acid colloid is vacuum-bubbled, and then the polyether amide acid colloid is evenly coated on a glass plate with a scraper, and then placed in a high-temperature oven at 80°C to remove the solvent in the film for 12h to 18h; the process of thermal gradient heating for imidization treatment in step six is: first keep warm at 150°C for 1h, then keep warm at 200°C for 1h, then keep warm at 250°C for 1h, and finally keep warm at 300°C for 1h.